Characterizing protein–protein-interaction in high-concentration monoclonal antibody systems with the quartz crystal microbalance. Issue 48 (4th December 2017) - Hartl, Josef; Peschel, Astrid; Johannsmann, Diethelm; Garidel, Patrick
Abstract : Making use of a quartz crystal microbalance, concentrated solutions of therapeutic antibodies were studied with respect to their behavior under shear excitation with frequencies in the MHz range. Abstract : Making use of a quartz crystal microbalance (QCM), concentrated solutions of therapeutic antibodies were studied with respect to their behavior under shear excitation with frequencies in the MHz range. At high protein concentration and neutral pH, viscoelastic behavior was found in the sense that the storage modulus, G ′, was nonzero. Fits of the frequency dependence of G ′( ω ) and G ′′( ω ) ( G ′′ being the loss modulus) using the Maxwell-model produced good agreement with the experimental data. The fit parameters were the relaxation time, τ, and the shear modulus at the inverse relaxation time, G * (at the "cross-over frequency" ω C = 1/ τ ). The influence of two different pharmaceutical excipients (histidine and citrate) was studied at variable concentrations of the antibody and variable pH. In cases, where viscoelasticity was observed, G * was in the range of a few kPa, consistent with entropy-driven interactions. τ was small at low pH, where the antibody carries a positive charge. τ increased with increasing pH. The relaxation time τ was found to be correlated with other parameters quantifying protein–protein interactions, namely the steady shear viscosity ( η ), the second osmotic virial coefficient as determined with both self-interaction chromatography ( B 22, SIC ) and static light scattering ( B 22, SLS ), and the diffusion interaction parameter as determined with dynamic light scattering ( k D ). While B 22 and k D describe protein–protein interactions in diluted samples, the QCM can be applied to concentrated solutions, thereby being sensitive to higher-order protein–protein interactions.